Public Service Quality, Employee Ambidexterity, Women Leadership and Public Management of Government Organization - Mulyani, Ade (Ilomata International Journal of Management, 2025)
This study aims to describe the influence of public service quality, employee ambidexterity, and women leadership on public management of Bukittinggi City Government. This study used a comparative quantitative method. The location of the study was in the Bukittinggi City Government environment. The sample of this study was the leadership ranks, namely from echelon II. B to echelon IV. B totaling 209 people. The research instrument was a questionnaire. Data collection was carried out by distributing Google form questionnaires via WAg. The data analysis technique used the T-test. The conclusion of this study is that there is a significant influence of employee ambidexterity toward public management, women leadership toward public management, public service quality with employee ambidexterity, and public service quality toward women leadership. The limitations of this study lie in the research method that only used a quantitative approach, in addition, the research location is only limited to the Bukittinggi City Government environment. Recommendations for further research are to use mixed-method research methods, add contextual variables, and compare with international contexts.